A Unified Long-Run Macroeconomic Projection of Health Care Spending, the Federal Budget, and Benefit Programs in the US - John Mantus; Gaobo Pang; Mark J. Warshawsky (American Enterprise Institute (AEI), 2023)
In the official models for projections and policy analysis (used by the Treasury, the Social Security and Medicare Trustees, and the Congressional Budget Office (CBO)), many key variables are assumed as a continuation of past trends. By contrast, in our model, these variables are simultaneously determined by supply and demand, based on logical functional forms and parameter estimates from the literature or empirical analysis. This approach better reflects real economic relationships—between health care spending, the federal budget, and investment in capital—and changing underlying conditions, especially demographics. Within the next ten years, we find the federal government budget deficit will grow significantly beyond historical experience and should be regarded as unsustainable. We project that debt-to-GDP will be 135 percent in 2032 and 268 percent in 2052, compared to CBO's 112 percent and 177 percent, respectively. Real interest rates rise in the long run, ratcheting interest payments, deficits, and debt, and vice versa. Our projection of national health expenditures relative to GDP in 2072 is 31.4 percent, compared to 28.4 percent by the Centers for Medicare & Medicaid Services (CMS). These higher costs of health care arise from labor shortage effects in an aging economy because health care is produced in a low productivity, labor-dependent sector. Health care expenditure further deteriorates the federal budget and lowers consumer welfare.
Keywords: 330